Magnetic resonance imaging in prostate brachytherapy: Evidence, clinical end points to data, and direction forward - Pugh, Thomas J.; Pokharel, Sajal S. (Brachytherapy, 2017)
The integration of multiparametric MRI into prostate brachytherapy has become a subject of interest over the past 2 decades. MRI directed high-dose-rate and low-dose-rate prostate brachytherapy offers the potential to improve treatment accuracy and standardize postprocedure quality. This article reviews the evidence to date on MRI utilization in prostate brachytherapy and postulates future pathways for MRI integration.